2014
DOI: 10.5380/rsa.v15i1.41092
|View full text |Cite
|
Sign up to set email alerts
|

Interferência De Plantas De Cobertura Sobre a Incidência De Plantas Invasoras E a Produção De Cebola Sob Sistema De Plantio Direto

Abstract: RESUMOMesmo com expectativas de expansão das áreas agrícolas brasileiras sob sistema de plantio direto (SPD), são poucos os trabalhos sobre o controle de plantas invasoras sem o uso de herbicidas, principalmente na produção de hortaliças, como a cebola. Para tanto, culturas utilizadas para cobertura do solo se mostram eficientes no controle do desenvolvimento de plantas invasoras através da inibição física e/ou alelopática. O objetivo do presente trabalho foi avaliar diferentes espécies de cobertura do solo, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…O centeio é uma espécie com grande potencial para uso em cobertura de solo. Vilanova et al (2014), avaliando a interferência de plantas de cobertura sobre a incidência de plantas invasoras e a produção de cebola sob sistema de plantio direto, verificaram menor produção de matéria seca de plantas invasoras, com uso de centeio associado a nabo forrageiro para cobertura do solo. Além disso, plantas de centeio promovem maior agregação de solo e estruturação (MOORE et al 2014) e retenção de água (BASCHE et al 2016).…”
Section: Introductionunclassified
“…O centeio é uma espécie com grande potencial para uso em cobertura de solo. Vilanova et al (2014), avaliando a interferência de plantas de cobertura sobre a incidência de plantas invasoras e a produção de cebola sob sistema de plantio direto, verificaram menor produção de matéria seca de plantas invasoras, com uso de centeio associado a nabo forrageiro para cobertura do solo. Além disso, plantas de centeio promovem maior agregação de solo e estruturação (MOORE et al 2014) e retenção de água (BASCHE et al 2016).…”
Section: Introductionunclassified
“…Souza et al (2018) evaluated different cover crops under NTVS and found a higher weed suppression with rye, barley, or black oats, especially at the beginning of the onion cycle, when there is more competition by weeds. In another work carried out in the same area of our study, the treatments with oilseed radish, rye, or oilseed radish + rye had the highest cover crops yield, which resulted in lower weed dry matter at the beginning of the onion crop cycle (Vilanova et al 2014).…”
Section: Introductionmentioning
confidence: 48%
“…Cover crop species improve soil physical and chemical attributes in onion fields (Loss et al, 2017;Comin et al, 2018a;Santos et al, 2018;Ferreira et al, 2018) as well as soil biological properties (Silva et al, 2014). They also lead to lower weed emergence, affecting onion yield and quality (Vilanova et al, 2014;Oliveira et al, 2016;Comin et al, 2018b;Souza et al, 2018). However, successive onion crops can affect soil characteristics, which requires evaluating the long-term effects of soil management systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the persistence of radish dry matter on the soil was favored by the presence of grasses, such as rye, which contributed to a slower decomposition, probably due to the increase in the C/N ratio of the plant residue formed on the soil (Oliveira et al, 2016), hindering the emergence of weeds. In studies conducted by Vilanova et al (2014) in field experiments, it was observed that the lowest dry matter productions of spontaneous plants during the onion cycle in 2009 occurred in the intercropped radish + rye treatment during the first 30 evaluation days.…”
Section: Weed Emergence Dynamicsmentioning
confidence: 98%